Atherosclerotic Cardiovascular Disease in Diabetes Patients - Amelia, Rina; Sari Wahyuni, Arlinda; Yunanda, Yuki; Wijaya, Hendri (Current Diabetes Reviews, 2023)
Background: Diabetes mellitus (DM) is a metabolic disorder characterized by abnormally elevated levels of blood glucose. The hyperglycemic condition is caused by abnormalities in either insulin secretion, insulin action, or both. Two-thirds of diabetes-related deaths are caused by atherosclerotic cardiovascular disease (ASCVD). Objective: The purpose of this study was to determine the risk of ASCVD and related factors in type 2 DM patients in Medan, North Sumatra. Methods: We conducted a cross-sectional observational study. A total of 252 DM patients visiting primary health centers in Medan were recruited after fulfilling the inclusion and exclusion criteria. The level of risk of atherosclerotic cardiovascular disease (ASCVD) was determined by using ASCVD Risk Calculator. Data required to use this calculator are age, sex, race, total cholesterol, HDL-C, systolic blood pressure, diastolic blood pressure, history of diabetes, history of hypertension treatment, smoking history, and use of statins for anti-hyperlipidemia. The data were then analyzed with Chi-square Test (p < 0.0%) and processed with SPSS. Results: There were 59 (23.41%), 140 (55.56%), and 53 (21.03%) participants who had high, moderate, and low risks of ASCVD, respectively. Bivariate analysis showed significant association between risk of ASCVD with age, SBP, total cholesterol level, HDL-C levels, and duration of diabetes (p < 0.05). Meanwhile, gender and familial history not related to ASCVD risks among DM patients (p > 0.05). Conclusion: The risks for atherosclerotic complications of cardiovascular disease in type 2 DM patients in Medan were predominantly high. The variables related to ASCVD risks included age, gender, HbA1C, systolic blood pressure (SBP), total cholesterol levels, HDL-C, and LDL-C levels.
Keywords: risk estimator